Towards an Authentically Assessed Science Curriculum - Fensham, P.; Rennie, Leonie (Springer, 2013)
The intentions of the science curriculum are very often constrained by the forms of student learning that are required by, or are currently available within, the system of education. Furthermore, little attention is given to developing new approaches to assessment that would encourage these good intentions. In this chapter, we argue that achieving this broadening of the intentions of science education will require a diversity of assessment techniques and that only a profile of each student’s achievement will capture the range of intended learnings. We explore a variety of assessment modes that match some of these new aspects of science learning and that also provide students with both formative information and a more comprehensive and authentic summative profile of their performances. Our discussion is illustrated with research-based examples of assessment practice in relation to three aspects of science education that are increasingly referred to in curriculum statements as desirable human dimensions of science: context-based science education, decision-making processes and socioscientific issues and integrated science education. We conclude with some notes on what these broader kinds of assessment mean for teachers and the support they would need to include them in their day-to-day practices in the science classrooms if, and when, the mainstream of science teaching and learning takes these curricular intentions seriously.